2018
DOI: 10.1016/j.jvs.2018.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after first-time lower extremity revascularization for chronic limb-threatening ischemia in insulin-dependent diabetic patients

Abstract: Objective: Historically, open surgical bypass provided a durable repair among diabetic patients with chronic limbthreatening ischemia (CLTI). In the current endovascular era, however, the difference in long-term outcomes between first-time revascularization strategies among patients with insulin-dependent diabetes mellitus (IDDM) is poorly understood.Methods: We reviewed the records of all patients with IDDM undergoing a first-time infrainguinal bypass graft (BPG) or percutaneous transluminal angioplasty with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
(39 reference statements)
0
16
0
Order By: Relevance
“…Previously, insulin-treated diabetics have been demonstrated to present more severe disease at a relatively young age. 27 In this study, the median age for insulin users at revascularization was 72.4 (IQR: 64.0–79.5), which is significantly younger than in non-insulin diabetics and non-diabetics (NIT-DM 76.0, IQR: 67.9–83.6 versus non-DM 77.3, IQR: 68.5–83.7, p < 0.001). In the previous literature, insulin use has been particularly associated with a multitude of comorbidities.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Previously, insulin-treated diabetics have been demonstrated to present more severe disease at a relatively young age. 27 In this study, the median age for insulin users at revascularization was 72.4 (IQR: 64.0–79.5), which is significantly younger than in non-insulin diabetics and non-diabetics (NIT-DM 76.0, IQR: 67.9–83.6 versus non-DM 77.3, IQR: 68.5–83.7, p < 0.001). In the previous literature, insulin use has been particularly associated with a multitude of comorbidities.…”
Section: Discussionmentioning
confidence: 54%
“…This same treatment strategy of “endovascular first” has been reported in multiple studies and vascular centers. 27 29 In infrapopliteal CLTI patients overall, endovascular methods can be efficient in short and stenotic lesions, whereas long occlusions may require surgical revascularization for better outcomes. 3…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All patients with ulcers, gangrene or pain in the foot attributable to PAD should be considered for urgent care and should be referred Heavy calcifications, infra-popliteal vessel involvement, long and multilevel lesions, frequently associated foot infection and associated medical comorbidity render diabetics at much higher risk of major amputation. 11,12 Bypass surgery remains a more durable revascularisation option in relatively fit patients with expected life expectancy of > 2 years. 13 Recent studies have shown excellent results with bypass surgery in diabetics, both in the short and long term.…”
Section: Discussionmentioning
confidence: 99%